Heterogeneity and Immunochemical Properties of Anti-β2-glycoprotein I Autoantibodies - Arvieux, J.; Regnault, V.; Hachulla, E.; Darnige, L.; Roussel, B.; Bensa, J. C. (Thrombosis and Haemostasis, 1998)
Most anticardiolipin antibodies (ACA) associated with antiphospholipid syndrome (APS) are directed against epitopes expressed on β2-glycoprotein I (β2GPI). Despite a good correlation between standard ACA assays and those using purified human β2GPI as the sole antigen, some sera from APS patients only react in the latter. This is indicative of heterogeneity in anti-β2GPI antibodies. To characterize their reactivity profiles, human and bovine β2GPI were immobilized on γ-irradiated plates (β2GPI-ELISA), plain polystyrene precoated with increasing cardiolipin concentrations (CL/β2GPI-ELISA), and affinity columns. Fluid-phase inhibition experiments were also carried out with both proteins. Of 56 selected sera, restricted recognition of bovine or human β2GPI occurred respectively in 10/29 IgA-positive and 9/22 IgM-positive samples, and most of the latter (8/9) were missed by the standard ACA assay, as expected from a previous study. Based on species specificity and ACA results, IgG-positive samples (53/56) were categorized into three groups: antibodies reactive to bovine β2GPI only (group I) or to bovine and human β2GPI, group II being ACA-negative, and group III being ACA-positive. The most important group, group III (n = 33) was characterized by (i) binding when β2GPI was immobilized on γ-irradiated polystyrene or cardiolipin at sufficient concentration (regardless of β2GPI density, as assessed using 125I-β2GPI); (ii) and low avidity binding to fluid-phase β2GPI (Kd in the range 10–5 M). In contrast, all six group II samples showed (i) ability to bind human and bovine β2GPI immobilized on non-irradiated plates; (ii) concentration-dependent blockade of binding by cardiolipin, suggesting epitope location in the vicinity of the phospholipid binding site on native β2GPI; (iii) and relative avidities approximately 100-fold higher than in group III. Group I patients were heterogeneous with respect to CL/β2GPI-ELISA and ACA results (6/14 scored negative), possibly reflecting antibody differences in terms of avidity and epitope specificity. Affinity fractionation of 23 sera showed the existence, in individual patients, of various combinations of antibody subsets solely reactive to human or bovine β2GPI, together with cross-species reactive subsets present in all samples with dual reactivity namely groups III and II, although the latter antibodies were poorly purified on either column. Therefore, the mode of presentation of β2GPI greatly influences its recognition by anti-β2GPI antibodies with marked inter-individual heterogeneity, in relation to ACA quantitation and, possibly, disease presentation and pathogenesis.